Entrepreneurship Training and Voice Production Skills as Creative Industry Business Opportunities - Zabihollah Nademi; Reza Shirzadi (Community Service Akseprin Journal, 2024)
The problem that needs to be resolved through this service activity is that there is still a lack of students who are aware of the profit opportunities from sound production on the economy; There are students who do not understand how to produce sound production independently, and students who do not know the various types of sound production can be learned and obtained into a product that can be traded. The main target in this voice production training is student members from the University. Entrepreneurship and Sound Production Training uses training methods or workshops related to sound production. There are two main types of workshops, namely; Voice Production workshop, and Voice Production entrepreneurship workshop. The workshop included podcast, dubbing, voice over, and narrator training, as well as entrepreneurship training. The stages that will be carried out in training are preparation, training, and evaluation. The preparation stage discusses event preparation, time preparation and preparation of activity material content. Voice production training on indicators  and can mention the various hardware used in voice production recording is in the good category